Spectroscopic Investigation on the Binding of a Cyanine Dye with Transferrin. (19th October 2015) - Zhang, Xiu‐feng; Lan, Ling; Chen, Lei; Chen, Hong‐bo; Yang, Qian‐fan; Li, Qian; Li, Qi‐long; Sun, Xiao‐ran; Tang, Ya‐lin
Abstract: Transferrin (Tf) can control the level of free iron as iron‐binding blood plasma glycoprotein in biological fluids. Tf has been exploited in the recent years on account of the potential function as a drug carrier targeting to tumor cells.Cyanine dyes have been widely studied as photosensitizers. The binding mechanism of Tf with 3, 3′‐di(3‐sulfopropyl)‐4, 5, 4′, 5′‐dibenzo‐9‐ethyl‐thiacarbocyanine triethylammonium salt (ETC) was characterized at varying pHs and temperatures by fluorescence, UV‐Vis absorption, circular dichroism (CD), andmolecular modeling methods. The results showed that the static fluorescence quenching occurred between Tf and ETC. It was found that ETC bound strongly with Tf with an intrinsic binding constant ( Ka ), in the order of 10 7  m −1 . The thermodynamic parameters demonstrated that van der Waals force or hydrogen bonds were the major binding force. The binding of ETC‐Tf caused the secondary conformational change of Tf with increasing the α‐helix content in Tf, which was confirmed by the results of spectroscopic experiments.Molecular modeling revealed that ETC bound residues located in the N‐lobe of Tf by van der Waals force and induced local structural changes of Tf. This study may provide the theoretical foundations for ETC as a probe to label Tf, which is further beneficial to the Tf‐targeted drugs in viv o . Copyright © 2015 John Wiley & Sons, Ltd. Abstract : It was found that the binding mechanism of potential probe ETC with transferrin. The interaction is mainly governed by van der Waals force and is sensitive to pH. ETC bound strongly with residues located in the N‐lobe of transferrin by van der Waals force with an intrinsic binding constant in the highest order of 10 7 M −1 and induced local conformational changes in transferrin with increasing α‐helical content. It provides theoretical foundations for ETC as a probe to label transferrin.